Clinical Studies of Cell Therapy in Cardiovascular Medicine: Recent Developments and Future Directions. Issue 2 (6th July 2018) - Banerjee, Monisha N.; Bolli, Roberto; Hare, Joshua M.
Abstract : Given the rising prevalence of cardiovascular disease worldwide and the limited therapeutic options for severe heart failure, novel technologies that harness the regenerative capacity of the heart are sorely needed. The therapeutic use of stem cells has the potential to reverse myocardial injury and improve cardiac function, in contrast to most current medical therapies that only mitigate heart failure symptoms. Nearly 2 decades and >200 trials for cardiovascular disease have revealed that most cell types are safe; however, their efficacy remains controversial, limiting the transition of this therapy from investigation to practice. Lessons learned from these initial studies are driving the design of new clinical trials; higher fidelity of cell isolation techniques, standardization of conditions, more consistent use of state of the art measurement techniques, and assessment of multiple end points to garner insights into the efficacy of stem cells. Translation to clinical trials has almost outpaced our mechanistic understanding, and individual patient factors likely play a large role in stem cell efficacy. Therefore, careful analysis of dosing, delivery methods, and the ideal patient populations is necessary to translate cell therapy from research to practice. We are at a pivotal stage in the field in which information from many relatively small clinical trials must guide carefully executed efficacy trials. Larger efficacy trials are being launched to answer questions about older, first-generation stem cell therapeutics, while novel, second-generation products are being introduced into the clinical realm. This review critically examines the current state of clinical research on cell-based therapies for cardiovascular disease, highlighting the controversies in the field, improvements in clinical trial design, and the application of exciting new cell products.